Analisis Karakteristik Konsumen Dalam Keputusan Pembelian Keripik Balado (Studi Kasus Pada Usaha Keripik Balado Christine Hakim Kota Padang) - Gusvita, Herda; Gusriati; Sintia Rahmadani (Fakultas Pertanian, Universitas Ekasakti, 2023)
This study aims to study the characteristics of Christine Hakim's Balado Chips consumers and to analyze the effect of these characteristics on the purchasing decisions of Balado Chips at the Balado Christine Hakim Chips Business, Padang City. This research was conducted in July - August 2021. The population in this study were Christine Hakim's Balado Chips consumers, with the criteria that consumers were 17 years old and consumers who had purchased Balado chips at Christine Hakim's Balado Chips Business. The method of determining the respondents was done by accidental sampling with the number of respondents 35 people. The data used are secondary and primary data. The analytical tool used is multiple linear regression with SPSS Version 20.0 program. The results showed that the consumer characteristics of the Balado Christine Hakim Chips Business in Padang City were at most 28 years old as many as 13 people (37.14%), female sex as many as 19 people (54.29%), consumers' occupations as civil servants and private employees respectively. -each as many as 13 people (37.14%), consumer education, namely S1 as many as 27 people (77.14%), consumer income ie 4,800,000-5,800,000/month as many as 17 people (48.57%), and domicile consumers outside the city of Padang as many as 21 people (60.00%). Partially, the variable that has a significant effect on the decision to buy Balado chips at the Balado Chips Business, Christine Hakim, Padang City is the income variable (sig 0.000 <0.05). While the simultaneous effect (together) is the variable age, education, income and domicile, with a coefficient of determination of 0.646 (64.6%).